EXISTENCE AND STABILITY OF A DAMPED WAVE EQUATION WITH TWO DELAYED TERMS IN BOUNDARY - Zitouni, S.; Ardjouni, A.; Zennir, K.; Amiar, R. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
This paper considers a linear damped wave equation with dynamic boundary conditions where two feedback terms have a delay. In bounded domain, we first establish the question of well-posedness and uniqueness of the solution for the initial-boundary value problem, using semigroup arguments in kato:67,kato:76,pazy. Next, by introducing suitable Lyapunov functionals, exponential stability estimates are obtained under conditions on the delay terms.